ANALISIS IMPLEMENTASI KAPITASI BERBASIS PEMENUHAN KOMITMEN PELAYANAN DI PUSKESMAS KABUPATEN LANGKAT - Surya Fahmi Fahmi; Rahmat Alyakin Dachi; Daniel Ginting; Frida Lina Tarigan; Zulfendri Zulfendri (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
One effort to improve the quality of Puskesmas health services in the implementation of the National Health Insurance Program is the implementation of the Commitment Fulfillment Capitation (KBPK) payment, but in its implementation many puskesmas cannot reach the capitation payment target that should be received by the puskesmas as a Health Facility Level First (FKTP) implementing KBPK. A qualitative descriptive study has been conducted with a case study approach at the Puskesmas located in Langkat District, with the aim of explaining the availability of resources, the role of the cross-sector, the Officer Expectations and how the planning process is implemented at the Puskesmas in the context of implementing KBPKP by utilizing informants, among others: , P-Care Officer, and Person in Charge in the Langkat District Health Office and Health BPJS. The results of the study show that planning and meeting the needs of officers is still lacking, so the authors assume this is the reason for the low achievement of the implementation of KBPKP in Puskesmas in Langkat District, while the resources of facilities and infrastructure, as well as the role of Cross Sector are not a problem. It is recommended to the Langkat Regency Government and the Head of the Puskesmas to immediately compile a good plan so that the implementation of the KBPKP in the Puskesmas can run well.